Association of blood manganese and selenium levels with hepatic steatosis among adolescents: a nationwide cross-sectional analysis - You, Bin; Chen, Zhiyuan (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to investigate the association between blood manganese and selenium levels and hepatic steatosis among adolescents, using data from the National Health and Nutrition Examination Survey (NHANES) 2017–2023.MethodsA cross-sectional analysis was conducted using data from 2,459 adolescents (aged 12–19 years) with complete data on liver ultrasound transient elastography, blood manganese, and selenium levels. Hepatic steatosis was defined as a controlled attenuation parameter (CAP) score of ≥248 dB/m, a measure of liver steatosis, which is a primary characteristic and a less severe stage of hepatic steatosis, assessed by vibration-controlled transient elastography (VCTE). Multivariate logistic regression models were used to assess the associations between blood manganese and selenium levels and hepatic steatosis, while restricted cubic splines (RCS) were employed to examine the dose-response relationships.ResultsThe mean age of the participants was 15.37 years, with 52.22% boy. Higher blood manganese and selenium levels were significantly associated with an increased prevalence of hepatic steatosis. In the fully adjusted model, adolescents in the highest quartile of blood manganese had more than twice the odds of hepatic steatosis compared to those in the lowest quartile (OR = 2.41, 95% CI: 1.55–3.75, P < 0.01). Similarly, the highest quartile of blood selenium was associated with a 57% increase in hepatic steatosis prevalence compared to the lowest quartile (OR = 1.57, 95% CI: 1.19–2.08, P < 0.01). RCS analysis confirmed a linear association between both blood manganese and selenium levels and hepatic steatosis prevalence. Subgroup analyses did not reveal statistically significant interactions by age, sex, or obesity status, although associations appeared stronger in younger adolescents.ConclusionElevated blood manganese and selenium levels are associated with a higher prevalence of hepatic steatosis in adolescents. These findings suggest a potential role of trace elements in the development of hepatic steatosis, highlighting the need for further research to better understand the underlying mechanisms involved in liver fat accumulation in this population.